Digital Health Solutions for Chronic Illnesses: A Systematic Review of Mobile Health Apps and Quality Analysis with Mobile App Rating Scale - Gintarė Vaitkienė; Zyta Kuzborska; Milda Žukauskienė (Journal of Ageing and Longevity, 2022)
Currently, more than half of the adults worldwide have at least one chronic condition; however, poor medication adherence and self-management are observed. Tools, such as mHealth apps, may play a crucial role for millions of people in increasing the patients’ involvement in the treatment process. The purpose of this study is to evaluate the characteristics and quality of the existing mHealth apps for patients with various chronic conditions. The study was conducted from February 1 to March 31, 2022. The mHealth applications’ search was performed on the iOS platform, and 29 apps were included in the final analysis. The quality of apps was evaluated using Mobile App Rating Scale. The majority of the apps had symptom and medication tracking functionality. The mean score of apps’ overall quality was 3.45 (SD = 0.61) out of five, ranging from 2.04 to 4.50. The highest-rated category was the functionality of the app—3.75 (0.61); followed by aesthetics—3.67 (0.62); subjective quality—3.47 (0.88); engagement—3.33 (0.78); and information—3.04 (0.61). The study revealed that only a few high-quality apps for chronic condition management exist, and there is still some space for improvements.